PENGARUH PRODUK, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE SAMSUNG (Studi Kasus Mahasiswa Fakultas Ekonomi Unika Santo Thomas SU ) - Manullang, Ida M. (UNIKA Santo Thomas, 2017)
The purpose of this research is to analyze the effect of product, promotion and service quality partially and simultaneously to the decision of Samsung mobile phone purchase and to know the dominant influence of the three variables (product, promotion and service quality) to the decision of purchasing Samsung mobile phone. Benefits Research, for researchers to compare the theories that have been experienced so far through research conducted, as well as develop analytical thinking skills and critical to existing problems and For Researchers can then use the results of this study as a comparison to the theory of theory based on the results of research conducted. Number of samples 72 respondents, data collection methods through questionnaire and documentation, variables studied about the influence of Product, Promotion and Quality of Service Against Samsung Mobile Purchase Decision, method of data analysis with multiple regression. The results showed that multiple regression equation Y = 0,39 + 0,51X1 + 0,27X2 + 0,12X3, it means product, promotion and service quality have positive influence to decision of samsung mobile phone purchase. Of the three independent variables (product, promotion and service quality) which gives the biggest influence is the product variable. Based on t test, from three independent variables (Product, Promotion and Service Quality) only two significant variables to decision of samsung mobile phone purchase that is product and promotion variable while service quality is not significant. With the F test, of the three independent variables (Product, Promotion and Service Quality) have a significant influence on the purchasing decision of samsung mobile phone. Correlation coefficient of product variables, promotion, and quality of service to the purchase decision of 0.804 means the relationship of independent variables with very strong bound variable. Coefficient of determination (Adjusted R2) equal to 0,625 means, product variable, promotion, and quality of service together can explain equal to 62,5% while the rest 37,5% influenced by other variable besides product, promotion and service quality. Of the three independent variables (product, promotion, and quality of service) should increase the frequency of promotion and quality of promotional quality delivered and also improve the quality of service so that the effect on the decision to purchase mobile phone samsung higher. Based on the value of coefficient of determination (Adjusted R2) of 0.625 indicates that product variables, promotion, and service quality together can explain by 62.5% while the remaining 37.5% influenced by other variables. Based on this it is better to increase the role of the three independent variables because that can be explained only by 62.5%.